A stable 4-bit ALU design for printed devices. (24th January 2022) - Suk, JunHa; Ahn, ChanYeop; Mojahidul Ahsan, S M; Kim, SoYoung
Abstract: Printed devices fabricated using roll-to-roll (R2R) printing technology have been used in low-cost Internet of Things (IoTs), smart packaging and bio-chips. As the area of applications of printed devices broadens, arithmetic units in digital design need to be implemented. In this paper, we propose a stable 4-bit arithmetic logic unit (ALU) design using a minimum number of transistors that can overcome the limitations of printed devices. We propose the use of a 2:1 transmission gate (TG) multiplexer structure and hybrid 16T full-adder to construct the ALU. New design methods are applied to reduce the number of inverter stages added to overcome the voltage degradation. Using this approach reduces the total number of transistors used in the design from 276 to 153, compared to the conventional design, with significant improvements in delay and power performance.